A Comparative Analysis Of Vocational Education Students’ Self-Efficacy And Entrepreneurial Orientation Based On Entrepreneurial And Non-Entrepreneurial Family Backgrounds - Nurfauziah; Sutarsi Suhaeb; Elfira Makmur (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyse the differences in the influence of self-efficacy on entrepreneurial orientation among vocational high school (SMK) students based on family background, namely entrepreneurial families and non-entrepreneurial families. The background of this study is based on the high unemployment rate among SMK graduates and empirical findings that families play an important role in shaping entrepreneurial character. The research method used was a comparative quantitative approach involving 92 respondents consisting of 46 students from entrepreneurial families and 46 students from non-entrepreneurial families. The research instrument measured self-efficacy and three dimensions of entrepreneurial orientation: innovativeness, risk-taking, and proactiveness. Data analysis was performed through classical assumption testing and simple linear regression in each group. The results showed that self-efficacy had a positive and significant effect on entrepreneurial orientation in both groups. However, the strength of this effect differed markedly. In the entrepreneurial group, the R Square value reached 0.545 for Y₁ and 0.465 for Y₂, indicating that self-efficacy is a strong predictor of entrepreneurial orientation. Conversely, in the non-entrepreneurial group, the R Square value was only around 0.248, indicating that most of the variation in entrepreneurial orientation was explained by other factors. These findings indicate that entrepreneurial family experiences and environments strengthen the relationship between self-efficacy and entrepreneurial orientation. This study emphasises the important role of the family in shaping entrepreneurial character and has implications for vocational schools to strengthen experience-based learning for students without an entrepreneurial family background.